1994
DOI: 10.1111/j.1399-302x.1994.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in root canal microbiota during the development of rat periapical lesions

Abstract: Periapical lesions are reproducibly induced in rats by pulp exposure and infection from the oral cavity. Lesions expand rapidly between day 7 and day 15-20 (active phase), with slowed expansion thereafter. In the present study we characterized the root canal microbiota present during the active phase of lesion development in this system. The mandibular first molars of Sprague-Dawley rats were exposed on day 0. The teeth were extracted after 7 days (n = 10 animals) and 15 days (n = 10), and the microbiota prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 22 publications
3
44
0
4
Order By: Relevance
“…After determination of the important role of bacteria in the pathogenesis of pulp and periapical lesions (1,2), elimination of infection from the root canal system became the objective of endodontic treatment of teeth with necrotic pulp and periapical lesions (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…After determination of the important role of bacteria in the pathogenesis of pulp and periapical lesions (1,2), elimination of infection from the root canal system became the objective of endodontic treatment of teeth with necrotic pulp and periapical lesions (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the virulence and number of microorganisms present in RCs, acute or chronic inflammation may be established in the periapical region. 1,2 In infected primary teeth, lesions normally develop in the furcation area instead of around the tooth apex, which could be related not only to the high incidence of accessory furcation canals 3 but also to infections with certain bacteria at these sites. However, few studies have been performed using molecular methods to identify the presence of anaeroDeclaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
mentioning
confidence: 99%
“…Sundqvist (16) demonstrated that bacteria could only be isolated from intact traumatized teeth with associated periapical lesions and not from necrotic teeth without lesions. The nature of the rootcanal microbiota associated with periapical-lesion development has been reviewed extensively in humans (17)(18)(19)(20) and in nonhuman primates (21,22). These studies indicated that there is a strong correlation between infection of the root canal and development of apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%